2014
DOI: 10.4321/s1134-80462014000100002
|View full text |Cite
|
Sign up to set email alerts
|

Encuesta nacional sobre dolor en las urgencias hospitalarias

Abstract: C. Encuesta nacional sobre dolor en las urgencias hospitalarias. Rev Soc Esp Dolor 2014; 21(1): 3-15. ABSTRACTObjective: To determine the epidemiology and management of acute pain in the emergency services (ES) of Spanish hospitals.Method: Survey "on line" to doctors responsible for the ES from a sample of different types of hospital across the country. Aspects of pain epidemiology, assessment, institutional resources, types of treatments and specific training aspects in pain practitioners in the field of ES a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
2
0
2
Order By: Relevance
“…Remarkably, in the present study opiates were the least used analgesics to control pain in older patients. This is in line with the results of a previous survey about pain management in Spanish EDs answered by emergency physicians, which showed that major opiates were administered in 16.9% of patients with pain, weak opioids in 25.4% and paracetamol/NSAID in 72.3% [22]. The lack of sex differences in opioid use has recently been reported in a population-based study in which, despite the high variability in opioid use across different settings, men and women had a similar likelihood of receiving opioids [23].…”
Section: Discussionsupporting
confidence: 91%
“…Remarkably, in the present study opiates were the least used analgesics to control pain in older patients. This is in line with the results of a previous survey about pain management in Spanish EDs answered by emergency physicians, which showed that major opiates were administered in 16.9% of patients with pain, weak opioids in 25.4% and paracetamol/NSAID in 72.3% [22]. The lack of sex differences in opioid use has recently been reported in a population-based study in which, despite the high variability in opioid use across different settings, men and women had a similar likelihood of receiving opioids [23].…”
Section: Discussionsupporting
confidence: 91%
“…Designing an activecontrolled trial in this setting is challenging because of variability in the management of trauma pain nationally, regionally, and even at the local level within hospitals. 32 In Spain, there is no established standard analgesic treatment or clinical guidelines for the emergency treatment of trauma pain; thus, it was necessary to use a pragmatic open-label study design. The most frequently used analgesics in Spanish EDs are nonsteroidal antiinflammatory drugs (generally administered parenterally), with a relatively low level of opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, pain is one of the main reasons for consultation in both primary care and hospital emergencies (Arrebola, García‐Delgado, Labrador‐Barba, Orera‐Peña & Martínez‐Martínez, 2016; Caba‐Barrientos, Benito‐Alcalá, Montes‐Pérez, Aguilar‐Sánchez de la Torre‐Liébana, R., & Margarit‐Ferri, 2014). Despite the fact that acute pain plays an important protective biological role as an alarm mechanism which prevents further damage to the organism experiencing pain (Chapman & Vierck, 2017; López‐Silva, Sánchez‐de Enciso, Rodríguez‐Fernández & Vázquez‐Seijas, 2007), sometimes pain can arise due to the application of certain types of treatments and certain types of diagnostic tests (Barroso, Santos, Santos, Nunes & Lucas, 2020; Boerner, Birnie, Chambers et al ., 2015; Martín‐Pintado‐Zugasti, López‐López, González Gutiérrez et al ., 2017), therefore losing its protective value and becoming a potential barrier for the preservation of the organism's health.…”
Section: Introductionmentioning
confidence: 99%